Analytical studies on the hoop conjecture in charged curved spacetimes - Peng, Yan (The European physical journal. C, Particles and fields, 2019)
Recently, with numerical methods, Hod clarified the validity of Thorne hoop conjecture for spatially regular static charged fluid spheres, which were considered as counterexamples against the hoop conjecture. In this work, we provide an analytical proof on Thorne hoop conjecture in the spatially regular static charged fluid sphere spacetimes.